2017
DOI: 10.1111/1440-1630.12381
|View full text |Cite
|
Sign up to set email alerts
|

Listening to teachers: Views on delivery of a classroom based sensory intervention for students with autism

Abstract: Background/aim Occupational therapists consider the impact of autism spectrum disorder on occupational performance at school. Occupational therapists work with teachers to support student participation. Atypical sensory processing is common in children with autism. Therefore, collaborating with teachers to enable students with autism to appropriately process sensory information within classrooms may be necessary. This qualitative pilot study aimed to capture teachers' perceptions of using a Sensory Activity Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…Nineteen teachers from North South Wales, Australia, trained by occupational therapist to implement SAS identified their motivation for participating. Mills and Chapparo (2018) found that the teachers desired to acquire additional tools to help their students improve their focus and self-regulate in class. In addition, teachers were interested in finding evidence to the effectiveness of SAS (Mills & Chapparo, 2018).…”
Section: Approaches and Barriers To Implementing Sasmentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen teachers from North South Wales, Australia, trained by occupational therapist to implement SAS identified their motivation for participating. Mills and Chapparo (2018) found that the teachers desired to acquire additional tools to help their students improve their focus and self-regulate in class. In addition, teachers were interested in finding evidence to the effectiveness of SAS (Mills & Chapparo, 2018).…”
Section: Approaches and Barriers To Implementing Sasmentioning
confidence: 99%
“…Mills and Chapparo (2018) found that the teachers desired to acquire additional tools to help their students improve their focus and self-regulate in class. In addition, teachers were interested in finding evidence to the effectiveness of SAS (Mills & Chapparo, 2018). This information highlights the needs of the teachers and helps enhance future collaboration between the occupational therapist and teachers.…”
Section: Approaches and Barriers To Implementing Sasmentioning
confidence: 99%
See 3 more Smart Citations